2008
DOI: 10.1682/jrrd.2007.07.0108
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and psychological correlates of two domains of hopelessness in schizophrenia

Abstract: Abstract-Hopelessness is a widely observed barrier to recovery from schizophrenia spectrum disorders. Yet little is known about how clinical, social, and psychological factors independently affect hope. Additionally, the relationships that exist between these factors and different kinds of hope are unclear.To explore both issues, we correlated two aspects of hope, expectations of the future and agency, with stigma, clinical symptoms, anxiety, and coping preferences in 143 persons with a schizophrenia spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 43 publications
3
18
0
1
Order By: Relevance
“…That hope and patient activation are empirically related is consistent with studies emphasizing hope as an important factor for consumers' active engagement in recovery (Kirkpatrick et al, 2001;McCann, 2002). Similarly, prior research (Hoffman et al, 2000;Lysaker et al, 2008) has shown that individuals with low 12 hope tend to give up easier and are less involved in their recovery. It is plausible that hope can lead to increased activation and involvement in recovery.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…That hope and patient activation are empirically related is consistent with studies emphasizing hope as an important factor for consumers' active engagement in recovery (Kirkpatrick et al, 2001;McCann, 2002). Similarly, prior research (Hoffman et al, 2000;Lysaker et al, 2008) has shown that individuals with low 12 hope tend to give up easier and are less involved in their recovery. It is plausible that hope can lead to increased activation and involvement in recovery.…”
Section: Discussionsupporting
confidence: 75%
“…Alternatively, hopelessness has been linked with being less likely to take action (Lysaker et al, 2008;Hoffman et al, 2000). Together, these findings are consistent with Deegan's (1988) earlier contention that regaining hope is critical for treatment engagement.…”
Section: Hopementioning
confidence: 99%
See 1 more Smart Citation
“…Isso implica que o estigma internalizado está inversamente associado a sentimentos de esperança. A desesperança pode resultar na internalização do estigma ou em crenças estereotipadas sobre o transtorno mental (Lysaker, Salyers, Tsai, Spurrier, & Davis, 2008), assim como indivíduos autoestigmatizados podem não aderir ao tratamento prescrito por se sentirem sem esperança e achar que o tratamento não rende benefícios (Corrigan et al, 2006). Pesquisas futuras são necessárias para determinar por que a diminuição da esperança está relacionada ao estigma internalizado, mas não especificamente à experiência subjetiva de ser avaliado de forma inferior aos demais membros da sociedade, visto que não houve correlação significativa entre a EEH e a subescala Alienação da ISMI Brasil.…”
Section: Discussionunclassified
“…Hope has been identified as an integral factor in recovery for people with schizophrenia (Deegan, 1996;Noordsy et al, 2002;Resnick et al, 2005) and has been described as the most basic step to recovery, in that one must believe recovery is possible and begin to look to the future with optimism (Jacobson and Greenley, 2001). Greater hope has also been associated with reduced symptoms, improved social functioning, a greater sense of personal recovery, greater activation in psychiatric treatment, and better quality of life in people diagnosed with schizophrenia (Kukla et al, 2013a;Kukla et al, 2013b;Lysaker et al, 2004;Lysaker et al, 2008;Mashiach-Eizenberg et al, 2013;Oles et al, 2015).…”
Section: Introductionmentioning
confidence: 99%